Validity test of anti-c1q serum as diagnostic marker for lupus nephritis - Enrica, M; Tjandrawati, A; Rachmayati, S; Hamijoyo, Laniyati (Indonesian Journal of Rheumatology, 2016)
Background: Lupus nephritis is defined as renal involvement in systemic lupus erythematosus (SLE) patients and the most important cause of morbidity and mortality. The diagnostic criteria that used toÂ diagnose lupus nephritis are 1997 American Collegeof Rheumatology is 24 hours urine protein â¥500 mgÂ and/or cellular cast, but significant renal damage can occur without proteinuria or cellular cast. Anti-C1q is an autoantibody that is produced by a chronic alteration of C1q collagen domain. Anti-C1q is a new specific marker for renal marker.Objective: To determine the validity of anti-C1q serum by using 1997 American College of Rheumatology criteria as a gold standard.Â Methods: This is a cross sectional study, conducted in October to December 2014 at Hasan Sadikin Hospital Bandung. The subjects had systemic lupus erythematosus with and without renal involvement, based on 1997 American College of Rheumatology criteria for SLE.Results: There were 65 subjects included in this study, 64 subjects were female and 1 subject was male. The age average was 32 (SD 11.7) years old. As many as 66.2% subjects had been diagnosed with lupus erythematosus systemic at least 3 years. Twenty four hours urine protein was measured using spectrophotometry, urine sediment was examinedfor cellular cast, and anti-C1q serum was measured using micro enzyme linked immunosorbent assay. Based on American College of Rheumatology criteria, 34 subjects were classified as lupus nephritis group while 31 subjects were classified as non-lupus nephritis group. The area under the curve of anti-C1q was 0.610. The cut-off value used in this study was 10.43 U/ml.Â The sensitivity, specificity, positive predictive value,negative predictive value and accuracy of anti-C1q assay were 41.18%, 77.42%, 66.67%, 54.55% and 58.46% respectively.Conclusion: Anti-C1q assay, based on this study, hasa low sensitivity and medium specificity to detect lupusnephritis